2023
DOI: 10.21053/ceo.2022.01368
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Systemic Inflammatory Markers Based on Blood Cells and Polysomnographic Factors in Obstructive Sleep Apnea

Abstract: Objectives. Systemic inflammation plays a key role in the pathogenesis of obstructive sleep apnea (OSA); however, easy-to-use methods to evaluate the severity of systemic inflammation have yet to be developed. This study investigated the association between systemic inflammation markers that could be derived from the complete blood count (CBC) profile and sleep parameters in a large number of patients with OSA.Methods. Patients who visited our hospital’s Otorhinolaryngology Sleep Clinic between January 2017 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
2
2
0
Order By: Relevance
“…Both single-factor and Additionally, MLR was positively correlated with AHI scores (r=0.273, P<0.05), with an area under the ROC curve of 0.673, 95% CI (0.601-0.744), indicating a certain predictive value for OSAHS. Our research suggests that elderly patients with higher BMI, NLR, and SII levels are more likely to suffer from OSAHS, which is consistent with the findings of Senaratna et al 4,23,24 Zahide's study found that there was no statistically significant difference in the MLR between OSAHS patients and the normal population. 26 However, in our study, we observed a significant correlation between MLR and the occurrence…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Both single-factor and Additionally, MLR was positively correlated with AHI scores (r=0.273, P<0.05), with an area under the ROC curve of 0.673, 95% CI (0.601-0.744), indicating a certain predictive value for OSAHS. Our research suggests that elderly patients with higher BMI, NLR, and SII levels are more likely to suffer from OSAHS, which is consistent with the findings of Senaratna et al 4,23,24 Zahide's study found that there was no statistically significant difference in the MLR between OSAHS patients and the normal population. 26 However, in our study, we observed a significant correlation between MLR and the occurrence…”
Section: Discussionsupporting
confidence: 92%
“…Studies have shown that NLR is associated with the severity of OSAHS. 23 Some research has investigated the relevance of SII and SIRI in the development of OSAHS 24,25 . However, there is currently no reported research on the relationship between MLR, PIV, and the occurrence of OSAHS, nor comparative studies of the association between different inflammatory parameters and the development of OSAHS.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it has been shown that these indices provide more information about the presence of an inflammatory state when compared with individual blood cell types [ 36 ]. Multivariate analysis showed no significant associations between measures of disease severity, AHI, and simple or combined indices, although NLR and SII were associated with AHI in univariate correlation analysis, in accordance with previous studies [ 34 , 35 ].…”
Section: Discussionsupporting
confidence: 91%
“…However, only a few reports have evaluated the prognostic capacity of these indexes, primarily NLR and PLR, with conflicting results [ 18 , 22 ]. The investigation of the systemic inflammatory response index (SII) in OSA was performed only in two studies reporting a significant positive correlation between AHI and SII [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…7,8 They often were regarded as easily measurable biomarkers of inflammation and oxidative stress in OSA, such as neutrophils, lymphocytes, monocytes, hemoglobin, and hematocrit, as well as new biomarkers including neutrophil to lymphocyte ratio (NLR), platelet to lymphocyte ratio (PLR), and systemic inflammatory index (SII). [9][10][11] In addition, immune cell-driven inflammation also plays a crucial role in the pathogenesis of OSA. Some pro-inflammatory markers released by peripheral blood cells such as C-reactive protein (CRP), interleukin (IL)-6, tumor necrosis factor-alpha (TNF-α), erythrocyte sedimentation rate (ESR) were also strongly associated with OSA severity.…”
Section: Introductionmentioning
confidence: 99%